2020
DOI: 10.3390/nu12092630
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physical Activity Practice and Adherence to the Mediterranean Diet in Relation to Multiple Intelligences among University Students

Abstract: Physical activity is important at any time of life. Particularly in the university, people tend to have more sedentary life, due to their studies. Eating habits are another health factor to consider. In addition, the Multiple Intelligences theory is a proposal that seeks the integral development and well-being of people. A descriptive, cross-sectional, and non-experimental research with the purpose of this study is to establish the relationships between practice of physical activity and the intelligences and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 57 publications
4
21
0
2
Order By: Relevance
“…Continuing with the relationship between age and psychological well-being, it is observed that participants who meet the criteria for physical activity reflect a positive relationship, to the detriment of those who do not meet the criteria. Given these findings, Veldema and Jansen (2019) suggest that the practice of physical activity has a positive impact on the physical and mental health of individuals, regardless of the age of the participants, due to the segregation of neurotransmitters during its practice (Ubago-Jiménez et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Continuing with the relationship between age and psychological well-being, it is observed that participants who meet the criteria for physical activity reflect a positive relationship, to the detriment of those who do not meet the criteria. Given these findings, Veldema and Jansen (2019) suggest that the practice of physical activity has a positive impact on the physical and mental health of individuals, regardless of the age of the participants, due to the segregation of neurotransmitters during its practice (Ubago-Jiménez et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes pertaining to emotional intelligence reveal that participants who engage in more than three hours of physical activity a week demonstrate better outcomes. In this sense, Vaquero-Solís et al [ 33 ] conclude that emotional clarity, together with the attention given to the negative feelings experienced during physical activity, helps to channel disruptive emotions due to the division of neurotransmitters [ 48 ]. In contrast, better relationships between emotional attention and repair were shown in participants who do not engage in more than three hours of physical activity a week.…”
Section: Discussionmentioning
confidence: 99%
“…Respecto al análisis relacional, se observa una relación negativa entre el clima tarea y la ansiedad, siendo estos resultados muy similares a los obtenidos por Kerstajn et al (2018) afirmando que cuando la práctica de actividad física se orienta hacia motivaciones de carácter intrínseco se consigue utilizar el ejercicio físico como un fin para canalizar estados disruptivos, siendo esto debido a la segregación de neurotransmisores (Ubago-Jiménez et al, 2020). Por el contrario, la relación existente entre el clima ego y la ansiedad es positiva, donde Lee et al (2021) que cuando la práctica deportiva se orienta hacia motivaciones de carácter extrínseco se fomentan los niveles de ansiedad, pudiendo perjudicar el rendimiento hacia la tarea (Kerstain et al, 2018).…”
Section: Discussionunclassified
“…Asimismo, también se observa una relación positiva entre el autoconcepto emocional y la ansiedad, siendo estos resultados muy diferentes a los concluidos por Conde-Pipó et al (2021) enunciando que una adecuada competencia emocional ayuda a canalizar estados perjudiciales para el bienestar. Finalmente, se observa una relación negativa entre el autoconcepto emocional y física, siendo estos resultados muy distintos a los obtenidos por Espejo-Garcés et al (2021), donde Ubago-Jiménez et al (2020) sostienen que la práctica de actividad física repercute positivamente en la imagen corporal de las personas y del bienestar emocional debido a la segregación de neurotransmisores como son la serotonina y dopamina…”
Section: Discussionunclassified